Catalytic oxidation of alcohols and alkyl benzenes to carbonyls using Fe3O4@SiO2@(TEMPO)-co-(Chlorophyll-CoIII) as a bi-functional, self-co-oxidant nanocatalyst. Issue 19 (25th September 2020) - Mahmoudi, Boshra; Rostami, Amin; Kazemnejadi, Milad; Hamah-Ameen, Baram Ahmed
Abstract : A new magnetically recyclable bi-functional self-co-oxidant based on a copolymer of TEMPO and chlorophyll has been developed for aerobic and selective oxidation of alcohols and alkyl benzenes. Abstract : Chlorophyll b was extracted from heliotropium europaeum plant, demetalated, allylated and grafted to acrylated TEMPO through a copolymerization protocol. Then, the chlorophyll monomers were coordinated to Co ions, immobilized on magnetic nanoparticles and the resulting hybrid was used as a powerful catalyst for a variety of oxidation reactions. By using the present method, oxidation of benzylic alcohols and alkyl benzenes to carbonyls was accomplished in water under aerobic conditions. Moreover, direct oxidation of alcohols to carboxylic acids was performed by adding NaOCl to the mixture. All entries were oxidized to the corresponding desired product with high to excellent yields and up to 97% selectivity. The catalyst was thoroughly characterized by CV, TGA, VSM, XRD, XPS, DLS, FE-SEM, TEM, UV-Vis, EDX, and BET analyses. The activity of the catalyst was investigated by applying various components of the catalyst to the oxidation model separately. The reasonable mechanisms are suggested based on the cooperation between the TEMPO groups and cobalt(iii ) (or Co(iv )) sites on the catalyst. The catalyst could be recovered and reused for at least 7 consecutive recycles without any considerable reactivity loss.